Determinan Kejadian Dermatitis Kontak Iritan pada Petani terpapar Pestisida di Desa Pallantikang - Ekasari, Ranti; Susilawaty, Andi; Jusriani, Rini (Jurnal Kesehatan, 2024)
Agriculture is one of the most common jobs in the informal sector as a source of livelihood to support the lives of people in Indonesia. However, the behaviour of workers in this industry is still far from good towards risk management and optimal management. One of the health problems that farmers often experience is the problem of irritant contact dermatitis. Irritant contact dermatitis is also an occupational disease in the agricultural sector. Personal hygiene, such as proper hand washing with soap and running water, is one of the factors that has a major impact on the incidence of contact dermatitis. The purpose of this study was to determine the variables that influence the incidence of irritant contact dermatitis in farmers in Pallantikang Village, Jenneponto District. This research is a quantitative research with cross sectional study design. This research was conducted in Pallantikang Village, Jeneponto Regency, South Sulawesi Province. The total sample size was 384 farmers. Farmers aged >45 years had a 1.7 times higher risk of dermatitis than farmers aged 12-45 years. Farmers who have been working for more than 5 years are at 1.5 times the risk of dermatitis than farmers who have been working for 0-5 years. Farmers who did not use PPE had a 1.7 times risk of suffering from dermatitis than farmers who used PPE such as masks. It is expected that health workers at the local health centre provide counselling to farmers regarding the toxic hazards that exist in the pesticides used by farmers and the prevention that can be done to minimise their impact such as the use of PPE so that dermatitis symptoms can be avoided.